Plasticity of thermal tolerance and associated gill transcriptome in ballan wrasse (Labrus bergylta) - Palma, Peter Almaiz; Bekaert, Michaël; Gutierrez, Alejandro P.; Abacan, Elfred John C.; Migaud, Herve; Betancor, Mónica B. (Frontiers in Marine Science, 2025)
Thermal condition has profound influence on physiology and behaviour of ballan wrasse (Labrus bergylta), a cleaner fish commonly deployed in salmon cages to control sea lice infection. To address knowledge gaps on the species thermal biology, critical thermal limits were determined by acclimating fish (21.5 ± 3.1 g, 10.5 ± 0.4 cm) at a range of temperatures (6, 10, or 14°C) found in its natural habitat on the west coast of Scotland for one week and subjecting them to ramping temperature ( 0.3°C/min) until loss of equilibrium. Critical thermal maxima (CTmax), minima (CTmin), and thermal breadth values increased with acclimation temperature. Thermal tolerance polygon was constructed and showed the intrinsic (7.9 to 16.8°C) and acquired (3.4°C and 22.8°C) thermal tolerance zones, supporting the seasonal differences in behaviour and delousing efficacy of ballan wrasse deployed in salmon farms. Gill transcriptomic profiles of ballan wrasse were performed following thermal acclimation and subsequent exposure to CTmax and CTmin. Initial acclimation resulted in unique differentially expressed genes (DEGs) and enrichment of GO terms that were almost exclusively found in each acclimation group. Transcriptome response to CTmax and CTmin also varied between acclimation groups. CTmax and CTmin shared 0% DEGs at 6°C, 43% at 10°C, and 7% at 14°C, but some overlapping GO terms. This study is the first to investigate the thermal tolerance limits of ballan wrasse and provides new data into the plasticity of thermal tolerance limits and molecular response to thermal stimuli in fish.